A COMPARATIVE STUDY OF NATIVE AND BORROWED LAYERS IN ENGLISH AND UZBEK LEXICAL SYSTEMS BASED ON LEARNER'S EXPLANATORY DICTIONARIES (International journal of artificial intelligence, 2025)
This article presents a comparative analysis of the native (indigenous) and borrowed (foreign origin) lexical layers in the lexical systems of English and Uzbek languages, based on explanatory learner’s dictionaries. The dictionaries selected as research material systematically analyze the origin, meaning, and structure of both native and borrowed lexical elements in the vocabulary of the two languages. The findings provide an in-depth understanding of the similarities and differences in the lexical structures of English and Uzbek. Additionally, the study highlights the cultural and historical significance of these lexical layers and their role in the development of language. The comparative analysis of these layers is of great importance for linguistic theory and language education. The study examines the features of native and borrowed lexical components based on learner’s explanatory dictionaries of English and Uzbek.